Modern weapons and military equipment for issue 3/2014 - Vučković, Dragan M. (Vojnotehnički glasnik / Military Technical Courier, 2014)
Buying protection/new submarines for Asia-Pacific region Formula for success/New algorithm KdV India and beyond/BrahMos India’s supersonic cruise missile Tanked up: enhancing capability and extending service lives